Pembelajaran Berdiferensiasi pada Mata Kuliah Bahasa Indonesia Konsep Kurikulum Merdeka-Kampus Merdeka di Perguruan Tinggi Vokasi - Husni Bt Salam (Mathematics Education Study Program, 2024)
The concept of Independent Learning - Independent Campus is a policy in learning that needs to be integrated into the Indonesian Language course based on differentiation. The purpose of this study is to describe differentiated learning in the Indonesian Language course. This research is classified as qualitative research with a case study design that occurred at the LP3I Makassar Polytechnic using an empirical approach. Data were collected from primary and secondary data sources through document study methods, observations, and in-depth interviews. Data analysis was carried out using inductive and argumentative techniques as the basis for implementing verification and drawing conclusions. The results show that differentiated learning in the Indonesian Language MKWK at the LP3I Makassar Polytechnic is emphasized in 3 (three) aspects, namely differentiation in terms of content, process, and product. The content in the Indonesian Language MKWK is diverse, such as speeches, orations or news in the mass media. Process differentiation is carried out by applying various learning models and methods, both inside and outside the classroom. Product differentiation can be seen from the diversity of outputs as a result of project learning carried out by. The obstacles faced in this differentiated learning include time constraints and teacher competence. Thus, it can be concluded that differentiated learning provides an opportunity to package learning in a varied way that can be integrated into the Merdeka curriculum.